2015
DOI: 10.1007/s10973-015-4427-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and flammability study of polystyrene composites containing magnesium–aluminum layered double hydroxide (MgAl–C16 LDH), and an organophosphate

Abstract: The flame retardancy and thermal stability of polystyrene compounded with Bis(2,4-dicumylphenyl) pentaerythritol diphosphate (DPP) and or a palmitate containing magnesium aluminum LDH (MgAl-C16 LDH) were investigated via thermogravimetric analysis, cone calorimetry, and pyrolysis combustion flow calorimetry. Cone calorimetry and thermogravimetry measurements revealed that the addition of 5 and 10 mass% of MgAl-C16 LDH to PS resulted in substantial reduction in peak heat release rate (PHRR) (47 and 61 %, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
(73 reference statements)
2
7
0
Order By: Relevance
“…Mono substituted benzene are obtained at δ(C-H)ar 756 cm −1 and γring 698 cm −1 . All these values are in accordance to corresponding literature data [41,42].…”
Section: Characterization Of the Ps/mmteo Nanocompositessupporting
confidence: 92%
“…Mono substituted benzene are obtained at δ(C-H)ar 756 cm −1 and γring 698 cm −1 . All these values are in accordance to corresponding literature data [41,42].…”
Section: Characterization Of the Ps/mmteo Nanocompositessupporting
confidence: 92%
“…They reported that the flame retardancy was improved by 50.6% for PS/Mg-Al LDH 5% composition. Enhanced thermal and flammability properties for the PS/LDH composites have also been conveyed by other researchers (Majoni 2015;Tai et al 2011). Adopting in situ thermal polymerization, Yeh et al (2004) prepared a series of PS/clay composites and inferred improved anticorrosive and thermal characteristics of the nanocomposites.…”
Section: Introductionmentioning
confidence: 77%
“…Hence, the reinforcing effect of these methods on the compatibility between LDHs and asphalt is limited. Silane coupling agents, often used to bridge organic and inorganic materials [ 21 , 22 ], have been employed to modify the organic surface of LDHs in some studies, and show effectiveness in improving the compatibility between LDHs and organics (e.g., polymethyl methacrylate, polystyrene, and epoxide resin) [ 23 , 24 , 25 , 26 , 27 ]. Based on this, silane coupling agents could be excellent modifiers to improve the dispersibility and stability of LDHs in hydrophobic asphalt matrix, and it has been reported in our previous studies that triethoxyvinylsilane (TEVS) surface organic LDHs could effectively improve the physical performances (penetration, softening point, ductility, etc.)…”
Section: Introductionmentioning
confidence: 99%